Study of the Child Autism's Impact on a Family Budget - S.S. Morozova; N.V. Tarasova (Moscow State University of Psychology and Education, 2022)
This article examined the effect of presence of a child with autism spectrum disorders (ASD) on the family budget. The article presents the effect on the structure of expenses, reveals which main factors the budget depend. The article considers the results of the response of 629 respondents from 43 regions of the Russian Federation and the Republic of Belarus to one of the questionnaire questions (more than 20 items in total): «You have a child with ASD in your family. How does this affect the family budget»? 8.3% of respondents do not note any impact of the child’s autism on the family budget; 46.4% («does not influence» and «affects tolerably») do not consider this impact as negative, 53.6% — as negative to varying degrees (including «negative» — 24.5%, «very negative» — 16.8%, «catastrophically negative» — 12.5%). It has been shown that the dependence of the negative impact on the economy of a family in which there is a child with autism is weak, although statistically significant (polychoric indicator of the relationship K = 0.12, P < 0.05) depends on the region of residence, and the economic well-being of the region (donor/recipient) is more affected, but the quality and range of services provided in the region to children with ASD and the families in which they grow up. The need to develop the expert community and state certification of support services for children with ASD and the quality of their provision was noted.